Reshaping Power Markets-Lessons from Chile and Argentina - Lalor, R. Peter; García, Hernán (World Bank, Washington, DC, 2012)
Power sector reforms in Chile and Argentina are now roughly fourteen and four years old. In both countries, restructuring and deregulation have increased efficiency, led to active entry by new generators, improved the quality of supply, and reduced prices in real terms. The authors' review of experience in both systems confirms that policymakers must apply effective measures to introduce and preserve competition. In Chile, a major concern is the predominance of one generator in one of the two systems.